ISLAM DAN HAK ASASI MANUSIA: ANALISIS TAFSIR MAUDHUI - Nila Sadiah; Muhammad Nawwarul Islam; Dr. Asep Abdul Muhyi, M.Ag (Najah Bestari, 2024)
Abstract Human rights and Islam are inseparable because most of the teachings of Islam contain values and teachings and laws about humanity and human rights. This article will discuss how a brief history of human rights in the west? How does Islam view human rights? and what is the conflict between syaria and human rights?. The study of Qur’an and tafsir is the formal object in this discussion while from the material point of view is the Islamic view of human rights sourced from the qor’an for tafsir maudhu’I application. The discussion of the Islamic view of human rights through a qualitative approach with an analytical descriptive method to obtain data and sources so that this study stat that the Islamic view of human as stated in the qur’an related to verves tat include human right are relevant. Keyword : Human rights, Islam, Maudhu’i